Nomination of Ministers According to the Areas of Electoral Support for Political Parties in Elections to the Chamber of Deputies of the Parliament of the Czech Republic - Dvořák Petr; Pink Michal (Politics in Central Europe, 2022)
Following identification of the areas of electoral support for the ruling parties since 1996 and subsequent analysis of the selection of ministers by each party, it was found that centre-right parties nominated more ministers from their areas of electoral support, mainly from Prague and other large cities. On the other hand, left-wing parties nominated ministers from similar areas to centre-right parties, even if they did not draw their electoral support from there. The Public Affairs party, which was established in Prague, nominated all its ministers from Prague, despite the fact that for the party it was not an area of electoral support. It is evident that, for the completion of a minister’s mandate, it is not important whether he or she comes from an area of electoral support. Only TOP 09, the Greens and KDU-ČSL (1998 elections) used the nomination of ministers to maximise votes within electoral regions, which could be identified as areas of electoral support in the previous elections. On the other hand, with ODA and ANO 2011, ministers were used outside the territory of electoral support, which may be related to the improvement of the election result in regions where the party was not so successful.